A vulnerabilidade externa decorrente da posição internacional de investimento e do fluxo de rendas: uma análise da economia brasileira no período de 1953-1963 - Noije, Paulo Van (2010)
This paper analyzes the external vulnerability of the Brazilian economy, especially in the financial sphere, arising from the International Investment Position and the flow of income for the period 1953 to 1963. Therefore, it is reported that the stocks of external assets and liabilities are determined by the balance of current account (obtained from the Balance of Payments) and the variations of the same value (which can not be obtained by the Balance of Payments), and presents a methodology alternative to the simple sum of flows to infer the values of liabilities and foreign assets, especially stocks of Foreign Direct Investment. In chapter 2 presents the International Situation of the period, marked by shortage of foreign currency, in a context which secured a strong growth through the Plano de Metas and incentives for foreign investment. Additionally, we demonstrated the reforms of the exchange period. Finally, the last chapter makes an analysis of key Balance of Payments for the period and an attempt of elaboration of the International Investment Position resulting from these flows and changes in value of inventories, obtained through the methodology presented in the first chapter. It is the deterioration of the external vulnerability of the Brazilian economy caused by the increase in net external liabilities. This increase was caused, according to the methodology employed, the proportion of: a) 68% because of shipping revenues, mainly by increasing the participation of interest at the expense of profits and dividends, b) 37% for other accounts current transactions except rents, c) and -5% for changes in value of stocks, especially by devaluations of foreign liabilities in the form of Foreign Direct Investment. Thus, the International Investment Position estimated during the period amounted to -6% in 1953 to -16% of Gross Domestic Product in 1963, due to the decrease in international reserves and the large increase of foreign debt, causing the resilience to external shocks of the Brazilian economy falls